Cunila jaliscana (Lamiaceae) a new species from Jalisco, Mexico - García-Peña, María Del Rosario; González-Gallegos, Jesús Guadalupe (Phytotaxa, 2013)
Cunila jaliscana, an endemic species to Jalisco, Mexico, is described and illustrated. Morphologically similar to C. lythrifolia, it differs by its divaricate branches, smaller leaf blades, narrower inflorescences, bracts shorter than calyx, and white and erect flowers.